Pupils in transition : moving between key stages - Nicholls, Gill (Routledge, 1999)
"Making the move from primary to secondary school is one of the major stepping stones in a young person's life. While there is a risk that some might find this move traumatic, there are many ways in which teachers can work to make the transition as smooth - and enjoyable - as possible. This book aims to help new and existing teachers to recognize the effects of transition, and to explore how schools can best ensure fluency at a time of change